Dampak Fluktuasi Nilai Tukar Terhadap Neraca Perdagangan Bilateral Indonesia Analisis Fenomena J-Curve - Tiara Ana Putri; Doni Satria (Universitas Negeri Padang, 2026)
This study aims to analyze the impact of exchange rate fluctuations on Indonesia's bilateral trade balance with Japan, the United States, India, Singapore, and China, and to test the existence of the J-Curve phenomenon and the Marshall-Lerner condition. The data used are quarterly data for the period 1993Q1–2024Q4 sourced from the IMF and other related agencies. The analytical method used is VECM with the Impulse Response Function analysis tool to identify the J-Curve. The results show that the J-Curve phenomenon is proven to occur in Indonesia's bilateral trade with Japan and the United States, so that the Marshall-Lerner condition is fulfilled in both countries, while in India, Singapore, and China the J-Curve phenomenon is not proven to occur. These findings indicate that the effectiveness of the exchange rate in improving the trade balance is highly dependent on the structural characteristics of each partner country's trade. This study provides an empirical contribution through the VECM approach on bilateral data with a long and comprehensive period coverage. The implications of this policy indicate that the effectiveness of exchange rate policy in improving Indonesia's trade balance needs to be supported by strengthening export capacity and implementing import substitution strategies.